School Inspection, quasi-market and government by the results (Avances en Supervisión Educativa, 2018)
The evolution from a bureaucratic regime to post-bureaucratic characterized by the emergence of quasi-market models and government by the results, together with the influence of the New Public Management, have contributed to generating a new scenario of administrative regulation by the State in the different educational systems, guided by reports and documents of certain international and national economic organizations, and in which the School Inspection must be placed professionally with concrete proposals for its debate.
Keywords: school inspection; administrative regulation; bureaucratic and post-bureaucratic regime; quasi-market; school results; New Public Management -NGP-; efficiency; equity; participation